Household Energy Poverty Assessment In Central And Eastern Indonesia - Akbar Setiawan; Zulfa Emalia; Irma Febriana MK (International Journal of Economics, Business and Innovation Research, 2024)
The phenomenon of energy poverty has been of particular concern around the world. This study was conducted to look at the determinants in the social and economic perspective of households that can affect energy poverty in the Central and Eastern Regions of Indonesia. This study uses panel data with a total of 80 data in the period 2018-2022. The variables used are per capita expenditure, education, working household head, house size, and number of household members as independent variables and energy poverty as the dependent variable. The results of the study show that per capita expenditure and house size have a significant effect of energy poverty. Meanwhile, education, working household head, and number of household members have no significant effect on energy poverty in Central and Eastern Indonesia.